Simulation and Environmental Assessment of Biodiesel Using Supercritical Methanol - Mohd Syakirin, Zulkarnain (2013)
Biodiesel is a recommended petroleum-based diesel substitute mainly because it is environmentally friendly and is renewable, domestic resource. In this thesis, supercritical methanol process to produce biodiesel from the rapeseed was design and simulate by using Aspen Plus v 7.0. Process flowsheets, along with detailed operating conditions and equipment design for this process was created. An environment assessment was also performed based on the result of process simulations and compare with heterogeneous catalyst method. WAR algorithm method is applied to perform environment assessment. The simulation results showed the supercritical process with 42:1 molar ratio and working at 3500C and 430 bar produce 997.91kg/h of FAME. . The environmental impact assessment shows the heterogeneous catalyst process show the least PEI result compare to supercritical methanol process which is indicate TRO 1552.33(with product) and TRO 1668.01(with product) respectively.